Membumikan Eco-Enzyme Kepada Masyarakat Kelurahan Air Putih Melalui Edukasi Dan Sosialisasi Pengolahan Sampah Organik Rumah Tangga - Deviona, Deviona; Chairul, Chairul; Nasrul, Besri; Tabrani, Gunawan; Nelvia, Nelvia; Armaini, Armaini; Marzuki, Salman; Sinaga, Raihan Daffansyah; Setiawan, Yayan; Sitompul, Diantika Elena; Febiani, Hartika; Rahimmi, Anna Fithra; Sandy, Athifah Faradilla; Khairunnisa, Syakira Nada; Annisa, Syarifah Sari (Journal of Community Engagement Research for Sustainability, 2023)
Lack of education in waste management has led to a large amount of waste being dumped in landfills. Organic waste is the largest type of waste disposed of in landfills. If organic waste is not managed properly, it can cause unpleasant odors in the environment and become a risk factor for global warming and explosions in landfills. This is also the case in RW 02 Air Putih Village. The community directly disposes of household waste without sorting the waste by type. In addition, the community also does not know how to process organic waste into useful items such as eco-enzyme and the products of eco-enzyme processing, namely liquid cleaning soap. This community service activity aims to increase community knowledge and skills on how to process household organic waste into eco-enzyme and cleaning liquid soap made from eco-enzyme as an effort to ground eco-enzyme. The targets in this activity are housewives in RT 01, RT 02, and RT 03, RW 02 Air Putih Village, Tuah Madani Subdistrict. The method used in this community service activity is socialization and training on how to make eco-enzyme and multipurpose cleaning liquid. The results obtained from this activity are the increased knowledge and skills of the community in processing household organic waste into eco-enzyme and liquid cleaning soap.